The Form Of Responsibility Of The Central Java Provincial Government In Fulfilling The Right To Mental Health of Nurses During The Covid-19 Pandemic - Fajar Widhi Atmojo (Universitas Duta Bangsa Surakarta, 2026)
The increase of Covid-19 cases has impacted in nurses, as the frontline in handling the Covid-19 pandemic, experiencing a physical health crisis and a mental health crisis. This is caused by the problem of ensuring the rights to health. The government is responsible for ensuring the right to health, including the right to mental health of nurses during the Covid-19 pandemic. This research aims to understand the regulations, implementation, and forms of government responsibility in fulfilling the right to mental health of nurses during the Covid-19 pandemic. This research was conducted in the Central Java Province. The research used a socio-legal descriptive-analytical approach. The data used were primary and secondary data obtained through interviews with the Deputy Head of the Regional Regulation Formation Agency of the Provincial Legislative Council of Central Java, the Head of Prevention and Infection Control at the Central Java Provincial Health Office, and the Indonesian Psychiatric Nurses Association of Central Java. The data from the research were analyzed using qualitative methods. The research results show that there is no void of norms from the highest to the lowest norms. Furthermore, there are no conflicts between norms, and there is no legal inequality related to the responsibility of the Central Java Provincial Government in fulfilling the rights to mental health for nurses during the Covid-19 pandemic. The Central Java Provincial Government fulfills its responsibility by giving mandates to the health department and IPKJI (Indonesian Psychiatric Association) for the fulfillment of nurses' mental health rights during the Covid-19 pandemic. The form of responsibility undertaken by the Central Java Provincial Government in fulfilling nurses' mental health rights includes efforts in mental and psychosocial health, namely from promotive, preventive, curative, and rehabilitative aspects. All of these are regulated under the Central Java Governor Regulation Number 25 of 2020 concerning the Control of Infectious Diseases in Central Java Province. However, with the enactment of the Health Omnibus Law (Rancangan Undang-Undang Kesehatan or omnibuslaw) by the DPR (People's Representative Council), there is a risk that mental health efforts will no longer be comprehensive and may remove the principle of lex specialis derogat legi generali, potentially leading to problems in fulfilling the rights to mental health.